Pseudomonas cannabina pv. alisalensis Virulence Factors Are Involved in Resistance to Plant-Derived Antimicrobials during Infection - Nanami Sakata; Takumi Haraguchi; Shunsuke Masuo; Takako Ishiga; Yasuhiro Ishiga (Plants, 2022)
Bacteria are exposed to and tolerate diverse and potentially toxic compounds in the natural environment. While efflux transporters are generally thought to involve bacterial antibiotic resistance in vitro, their contributions to plant bacterial virulence have so far been poorly understood. Pseudomonas cannabina pv. alisalensis (Pcal) is a causal agent of bacterial blight of Brassicaceae. We here demonstrated that NU19, which is mutated in the resistance-nodulation-cell division (RND) transporter encoded gene, showed reduced virulence on cabbage compared to WT, indicating that the RND transporter contributes to Pcal virulence on cabbage. We also demonstrated that brassinin biosynthesis was induced after Pcal infection. Additionally, the RND transporter was involved in resistance to plant-derived antimicrobials and antibiotics, including the cabbage phytoalexin brassinin. These results suggest that the RND transporter extrudes plant-derived antimicrobials and contributes to Pcal virulence. We also found that the RND transporter contributes to Pcal virulence on Brassicaceae and tomato, but not on oat. These results suggest that the RND transporter contributes to Pcal virulence differentially depending on the host-plant species. Lastly, our expression-profile analysis indicated that the type-three secretion system (TTSS), which is essential for pathogenesis, is also involved in suppressing brassinin biosynthesis. Taken together, our results suggest that several Pcal virulence factors are involved in resistance to plant-derived antimicrobials and bacterial survival during infection.